If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5) + -2x = 15 Reorder the terms: 3(5 + x) + -2x = 15 (5 * 3 + x * 3) + -2x = 15 (15 + 3x) + -2x = 15 Combine like terms: 3x + -2x = 1x 15 + 1x = 15 Add '-15' to each side of the equation. 15 + -15 + 1x = 15 + -15 Combine like terms: 15 + -15 = 0 0 + 1x = 15 + -15 1x = 15 + -15 Combine like terms: 15 + -15 = 0 1x = 0 Solving 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '1'. x = 0 Simplifying x = 0
| 6x-77+2x=43 | | -16/9=-8u | | 7x-2(1+3x)=2 | | 18+5w=3w-10 | | 5y-3/5=4/3 | | -(3v+4)=6v-3(3v+2) | | 77+4x=43 | | -2x(3x+4)+y=0 | | 0+1x=0.2(x+2) | | 3W-6+6W=-2+W | | -2/3t=6 | | 5x-x=12+6x | | 9w-2=-1w-22 | | -x-40+4x=26 | | 7v/6=-35 | | 4(x-5)+4(x-5)+3(x+6)+3(x+6)= | | 8y+9y-y-4+1y-4y=36 | | 5n-7=5(n+2)+3 | | A=pt-3p | | 1/2-3=9 | | 9(8-12w)= | | 5(x-3)=-(15-5x) | | -68+4x+3x=114 | | 5x/2=-3x+11 | | 5p-2(4-2p)=19 | | Y=-2+-0.6666666667x | | -3/7w=9 | | 2x-(2-x)=13 | | x=(2m-4)/(1+n) | | 125^-2/3 | | 7x^2+40x+25=0 | | 9x-8x-10=13 |